Public investment in defense and technological progress: a DSGE model - Jiménez, José Lorenzo; Fonfría, Antonio (Papeles de Europa, 2017)
This paper argues the importance of investment in defense, as part of public investment in enhancing the industrial and technological base of the country as well as in the development of innovative productive sectors. The analysis is performed through models of dynamic stochastic general equilibrium (DSGE). The main conclusion is that the increase in public investment, when it is complementary to the technological progress associated with private investment, translates into higher growth of production, employment, investment and productivity in the whole economy. Accordingly, to the extent that public investment in defense is generating innovation and technological progress, also it contributes positively to growth.